Targeting the Notch Signaling Pathway in Chronic Inflammatory Diseases - Christopoulos, Panagiotis F.; Gjølberg, Torleif T.; Krüger, Stig; Haraldsen, Guttorm; Andersen, Jan Terje; Sundlisæter, Eirik (Frontiers in Immunology, 2021)
The Notch signaling pathway regulates developmental cell-fate decisions and has recently also been linked to inflammatory diseases. Although therapies targeting Notch signaling in inflammation in theory are attractive, their design and implementation have proven difficult, at least partly due to the broad involvement of Notch signaling in regenerative and homeostatic processes. In this review, we summarize the supporting role of Notch signaling in various inflammation-driven diseases, and highlight efforts to intervene with this pathway by targeting Notch ligands and/or receptors with distinct therapeutic strategies, including antibody designs. We discuss this in light of lessons learned from Notch targeting in cancer treatment. Finally, we elaborate on the impact of individual Notch members in inflammation, which may lay the foundation for development of therapeutic strategies in chronic inflammatory diseases.